Balancing AI’s Promise and Pressure: A Dual-Process Model of AI Adoption Psychological States, and Employee Performance in Indonesia - Asmini Asmini (National Research and Innovation Agency, Indonesia, 2025)
This study investigates how artificial intelligence (AI) adoption affects employee performance through two competing psychological mechanisms: a positive pathway involving technological self-efficacy and job engagement, and a negative pathway involving perceived job insecurity and AI-induced stress. Drawing on data from 280 Indonesian employees across diverse sectors, the study employs structural equation modeling using SmartPLS to examine the hypothesized relationships. The findings confirm the dual-process model, showing that AI adoption positively influences performance by enhancing confidence in technology use and fostering engagement. However, the results also reveal that AI adoption can trigger job insecurity and psychological stress, which in turn negatively impact employee performance. Both sequential mediations positive and negative are statistically significant, emphasizing the coexistence of opportunity and risk in AI-driven transformation. These results contribute to theory by integrating cognitive-motivational and emotional-threat perspectives within the same framework. Practically, the study highlights the importance of organizational strategies that simultaneously empower employees through digital skill development while mitigating fears and emotional strain associated with technological disruption. The findings are particularly relevant to emerging economies like Indonesia, where rapid AI diffusion is not always matched by institutional protections or workforce readiness. Recommendations for inclusive, human-centered AI implementation are discussed